Impact of access to credit on income and food security in Malawi - Diagne, Aliou (International Food Policy Research Institute, 1998)
The paper departs from the standard practice that takes the estimated marginal effects of either the amount of credit received or membership in a credit program as measures of the impact of access to credit on household welfare. The marginal effects of the formal credit limit variable on household welfare, controlling for the credit limit from informal sources as well as the credit demanded from both sources, measure the marginal effects of access to formal credit. The main finding of the paper is that access to formal credit, by enabling households to reduce their borrowing from informal sources, has marginally beneficial effects on household annual income. However, these effects are very small and do not cause any significant difference between the per capita incomes, food security, and nutritional status of credit program members and noncurrent members. Moreover, the beneficial substitution effect reflects only the fact that reduced borrowing from informal sources makes informal loans play a lesser role in the negative impact that borrowing (from formal or informal sources) has on net crop incomes. The marginal effects on household farm and nonfarm incomes resulting from mere access to formal credit (without necessarily borrowing) are positive and quite sizable, but not statistically significant. Land scarcity and unfavorable terms of trade for the smallholders’ farm products remain by far the factors that most constrain per capita household income growth in Malawi. The paper concludes that the necessary complementary resources and economic environment are not yet in place for access to formal credit to realize its full benefits for Malawi’s rural population.